Model pengajaran M-Pembelajaran berasaskan kaedah inkuiri mata pelajaran sejarah peringkat menengah / Mohd Paris Saleh - Mohd Paris , Saleh (2016)
The purpose of the study is to develop an mLearning teaching model based on the inquiry method for the secondary school history subject. The construction of this model aims to show how mLearning combined with the inquiry method can be used to support the teaching of history. The study adopted the Design and Development Research Approach which was introduced by Ritchey & Klien (2007) to develop the model. Based on this approach, the study was conducted in three phases. Phase 1 involves a needs analysis using survey questionanaire that was conducted among 120 history teachers to investigate the need to adopt mLearning and consequently the development of this model. The data obtained were analyzed through descriptive statistic using the Statistical Package for the Social Sciences (SPSS) software.The Interpretation of of the data is based on the values of frequency and percentage. Phase 2 used the Interpretive Structural Modeling (ISM) method to develop the model based on views and decisions from panel of nine (9) experts. Data Interpretation was based on the model generated by ISM software and also via the classsification and network of relationships between the model elements (teaching activities). Phase 3 involves the evaluation of the model using a modified Fuzzy Delphi Technique by a panel of 30 people. The evaluation is based on experts responses to the 7 Likert scale questionnaire. Threshold (threshold ‘d’) are calculated to determine the experts consensus on all the items of the questionnaire while the deffuzzification values would be used to determine the decisions from the experts. Threshold value must exceed 75% or not more than 2.0 to determine the consensus among experts. While the defuzzyfication must be greater than 0.5 Theoverall findings of the first phase shows that teachers have at least one mobile device technology (100%, n = 120) of (74.2% = 89) with devices at least at level 2 (voice call capability,(SMS), video calls,receiving emails,surfing the internet,image and video recording and software to download). This means the history teachers have access to necessary technology for mLearning. The results also indicate the level of acceptance and intention ro the mLearning inquiry model. Therefore, studies for the construction of this model is required. Phase 2 results by the panel of experts has produced a model consisting of the teaching activities for the History subject. This activities relate to one another to form a mobile teaching model. The panel of esperts hold the view that the activity in the model can be divided into 3 part and 4 clusters of activities to facilitate the interpretation of the role of such activities. The results of phase 3, indicates that approval by the panel of experts is on (d = 86.9%) in the chosen teaching activities while the defuzzyfication values is greater than 0.5. This model proposes the teaching of history based on the inquiry method to be combined in practice through the mLearning to help history teachers become facilitators and motivators during lessons.